Metabolome-wide association study of flavorant vanillin exposure in bronchial epithelial cells reveals disease-related perturbations in metabolism. (February 2021) - Smith, Matthew Ryan; Jarrell, Zachery R.; Orr, Michael; Liu, Ken H.; Go, Young-Mi; Jones, Dean P.
Graphical abstract: Highlights: Vanillin in e-cig causes widespread metabolic disruption in airway epithelial cells. Metabolic disruption by vanillin is associated with lung disease. High-resolution metabolomics supports mechanistic toxicology of vanillin in e-cig. Abstract: Electronic cigarettes (e-cig) are an increasingly popular alternative to traditional smoking but have been in use for too short of a period of time to fully understand health risks. Furthermore, associated health risks are difficult to evaluate because of a large range of flavoring agents and their combinations for use with e-cig. Many flavoring agents are generally regarded as safe but have limited studies for effects on lung. Vanillin, an aromatic aldehyde, is one of the most commonly used flavoring agents in e-cig. Vanillin is electrophilic and can be redox active, with chemical properties expected to interact within biologic systems. Because accumulating lung metabolomics studies have identified metabolic disruptions associated with idiopathic pulmonary fibrosis, asthma and acute respiratory distress syndrome, we used human bronchial epithelial cells (BEAS-2B) with high-resolution metabolomics analysis to determine whether these disease-associated pathways are impacted by vanillin over the range used in e-cig. A metabolome-wide association study showed that vanillin perturbed specific energy, amino acid, antioxidant and sphingolipid pathways previously associated with human disease. Analysis of a small publicly available human dataset showed associations with several of the same pathways. Because vanillin is a common and high-abundance flavorant in e-cig, these results show that vanillin has potential to be mechanistically important in lung diseases and warrants in vivo toxicity testing in the context of e-cig use.